The psychological impact of fertility treatment suspensions during the COVID-19 pandemic - Gordon, Jennifer L. (PLoS One, 2020)
PURPOSE: To examine the psychological impact of fertility treatment suspensions resulting from the COVID-19 pandemic and to clarify psychosocial predictors of better or worse mental health. METHODS: 92 women from Canada and the United States (ages 20–45 years) whose fertility treatments had been cancelled were recruited via social media. Participants completed a battery of questionnaires assessing depressive symptoms, perceived mental health impact, and change in quality of life related to treatment suspensions. Potential predictors of psychological outcomes were also examined, including several personality traits, aspects of social support, illness cognitions, and coping strategies. RESULTS: 52% of respondents endorsed clinical levels of depressive symptoms. On a 7-point scale, participants endorsed a significant decline in overall quality of life (M(SD) = -1.3(1.3), p < .0001) as well as a significant decline in mental health related to treatment suspensions on a scale from -5 to +5 (M(SD) = -2.1(2.1), p < .001). Several psychosocial variables were found to positively influence these outcomes: lower levels of defensive pessimism (r = -.25, p < .05), greater infertility acceptance (r = .51, p < .0001), better quality social support (r = .31, p < .01), more social support seeking (r = .35, p < .001) and less avoidance of infertility reminders (r = -.23, p = .029). CONCLUSION: Fertility treatment suspensions have had a considerable negative impact on women’s mental health and quality of life. However, these findings point to several protective psychosocial factors that can be fostered in the future to help women cope.